REBOA for the Treatment of Blast Polytrauma: Zone 3 Provides Cerebral Perfusion, Attenuates Organ Dysfunction and Reperfusion Coagulopathy Compared to Zone 1 in a Swine Model. Issue 5 (6th May 2023) - Cralley, Alexis L.; Moore, Ernest E.; Sauaia, Angela; Carani, Pedro H.; Schaid, Terry R.; DeBot, Margot; Fragoso, Miguel; Ghasabyan, Arsen; Hansen, Kirk; Cohen, Mitchell J.; Silliman, Christopher C.; Fox, Charles J.
Abstract : In a blast polytrauma swine model, compared to AO Zone-1, Zone-3 provided similar neuro/cardioprotection but with less organ dysfunction and coagulopathy. This suggests Zone 3 may be preferable for treating blast polytrauma injuries not comorbid with abdomen or chest trauma. Abstract : BACKGROUND: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is a lifesaving therapy for hemorrhagic shock following pelvic/lower extremity injuries in military settings. However, Zone 1 aortic occlusion (AO; above the celiac artery), while providing brain/cardiac perfusion, may induce/worsen visceral ischemia and organ dysfunction. In contrast, AO Zone 3 (below the renal arteries) provides abdominal perfusion potentially minimizing ischemia/reperfusion injury. We hypothesized that, compared with AO Zone 1, AO Zone 3 provides neuro/cardioprotection while minimizing visceral ischemia and reperfusion coagulopathy after severe traumatic hemorrhage due to pelvic/lower extremity injuries. METHODS: Fifty-kilogram male Yorkshire swine underwent a blast polytrauma injury followed by a resuscitation protocol with randomization to no AO (No AO, n = 6) or AO with REBOA at Zone 1 (AO Zone 1; n = 6) or Zone 3 (AO Zone 3; n = 4). Vital signs and intracranial pressure (ICP) were monitored for 240 minutes. Citrate native and tissue plasminogen activator challenge thrombelastography, prothrombin time, creatinine, lipase, total bilirubin, troponin, and enzyme-linked immunosorbent assays protein levels were measured at set intervals. RESULTS: Both AO groups had significant increases in mean arterial pressure during aortic occlusion. All three groups had significant increases in ICP, but final ICP in the No AO group (26 ± 5.8 mm Hg) was significantly elevated compared with AO Zone 1 (17 ± 5.2 mm Hg) and AO Zone 3 (16 ± 4.2 mm Hg) ( p < 0.01). The final mean troponin in the No AO group (4.10 ± 5.67 ng/mL) was significantly higher than baseline (0.03 ± 0.02 ng/mL, p < 0.05), while the two AO groups had no significant changes ( p > 0.05). AO Zone 1 was the only group associated with hyperfibrinolysis ( p < 0.05) and significantly increased prothrombin time ( p < 0.05). Only AO Zone 1 group had significantly higher markers of organ damage. CONCLUSION: Compared with AO Zone 1, AO Zone 3 provided similar neuro/cardioprotection but with less organ dysfunction and coagulopathy. This study suggests that Zone 3 REBOA may be preferable over Zone 1 for treating military relevant blast polytrauma with minimal intra-abdominal and chest trauma, but further clinical investigation is warranted. Abstract :